Venous thromboembolism in burns patients: Are we underestimating the risk and underdosing our prophylaxis?. Issue 8 (August 2021) - Lu, Patrick; Harms, Karl-Anton; Paul, Eldho; Bortz, Hadley; Lo, Cheng; Cleland, Heather
Summary: Background: Burns patients exhibit all factors of Virchow's triad and are thus at high theoretical risk of venous thromboembolism (VTE). At our tertiary referral burns unit, a standard dose of low molecular weight heparin, which acts primarily by inhibiting Factor Xa, is given for thromboprophylaxis. However, the pharmacokinetics of enoxaparin are altered following a burn injury, and thus burns patients are likely underdosed on their thromboprophylaxis. The objectives of this study were to determine the incidence and risk factors for VTE among burns patients at the Victorian Adult Burns Service (VABS) and to determine the adequacy of the current enoxaparin thromboprophylaxis regimen through measurement of anti-factor Xa (AFXa) levels and comparison with established reference ranges. Methods: This study consisted of two parts. In part 1, the Burns Registry of Australia and New Zealand (BRANZ) was reviewed for cases of VTE in burns patients admitted to the VABS from 2013 – 2018. Part 2 was a prospective study that determined peak and trough AFXa levels in patients admitted to the VABS with >10% total body surface area (TBSA) burns. Results: Part 1. Totally, 1, 475 patients were admitted to the VABS between 2013 – 2018. There were 20 cases of VTE (1.36%). Percent TBSA of burn (OR = 1.04, 95% CI: 1.03 – 1.06), full thickness burns (OR = 2.78, 95% CI: 1.15 – 6.73), ICU admission (OR = 15.08, 95% CI: 5.01 – 45.44), mechanical ventilation (OR = 10.62, 95% CI: 4.05 – 27.91), operative procedures (OR = 1.43, 95% CI: 1.29 – 1.59), and a longer hospital stay (OR = 1.05, 95% CI: 1.04 – 1.07) were all associated with an increased VTE risk. Part 2. A total of 20 participants with >10% TBSA burns were recruited to the prospective study. Peak anti Factor Xa (AFXa) levels were measured for all 20 participants with 15% recording an initial prophylactic peak AFXa level within reference range. Upon subsequent measurements, 50% of participants reached a prophylactic peak AFXa level. Trough AFXa levels were measured for 17 participants with no participant recording an initial or subsequent trough AFXa level at or above the prophylactic threshold. Conclusion: Our study demonstrates a high incidence of VTE among burns patients at the VABS, especially among the major burns patients, and a thromboprophylaxis protocol that is ineffective in achieving prophylactic levels of AFXa level. The evidence suggests a need to evaluate different dosing protocols among burns patients in order to improve AFXa levels, with the aim of decreasing incidence of VTE in high-risk patients.